FIRST TRIMESTER URIC ACID LEVEL -A RISK FACTOR FOR GESTATIONAL DIABETES MELLITUS AND HYPOTHYOIDISM (Applied Biological Research, 2024)
Aim: To investigate the relationship between serum Uric acid concentration, gestational diabetes mellitus and to check the changes in thyroid hormone status with increased gestational age. Pregnant women with elevated uric acid levels are experiencing a higher occurrence of pregnancy complications like gestational diabetes mellitus (GDM) and sub clinical hypothyroidism.Materials and methods: About 50 non diabetic, Euthyroid pregnant women had participated in our study and 1st trimester Uric acid level was checked. Subsequently, all the pregnant women were continuously followed and OGCT, FT4, TSH was performed between 24-28 weeks of gestation.Results: Our study revealed a direct relationship between Glucose Challenge Test (GCT) results and serum uric acid levels, employing a threshold of more than 4.6mg/dl (p value
Keywords: Gestational diabetes mellitus; glucose challenge test; pregnancy; subclinical hypothyroidism; uric acid